Capital concentration in and through class differentiation: A case study from Pampean agribusiness - Christin Bernhold; Tomás Palmisano (Journal of Agrarian Change, 2021)
The National Agricultural Census (NAC) held in Argentina in 2018 shows that the concentration and centralization of agrarian capital in this country's heartland of grain and oilseed production is an ongoing process. An extensive academic literature has attributed this trend to the dynamics of capitalist development in agriculture in general and to Argentina's political economy in particular. Tying into these discussions and based on a case study, this paper argues that an analysis of how the growth of large corporations works in and through class differentiation helps to further explain the dynamics of concentration and centralization. This includes (i) examining the strategies of big companies to diversify capital functions across various value chain links and (ii) elucidating how they have established particular relations to smaller capitals, intermediate classes, and workers, as well as the related patterns of exploitation and appropriation of surplus value.
Keywords: 630; agribusiness; capital concentration; class analysis; Pampean region; value chains